Legal Protection Against Child Sexual Exploitation Through Augmented Reality and Virtual Reality Technology - Riri Rianza; Suriadi Sirait; Gusron Gusron; Muhamad Adystia Sunggara; Syafri Hariansah (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This research examines legal protection against child sexual exploitation through Augmented Reality (AR) and Virtual Reality (VR) technologies, which are increasingly developing in the digital era. AR combines virtual elements with the real world, while VR creates a fully immersive environment. Both offer positive opportunities and serious risks, including new crime modes such as the creation of avatars or virtual models of children for sexual purposes, grooming in virtual spaces, and the distribution of immersive child pornography. Anonymity, the difficulty of age verification, the lack of digital literacy, and the forensic challenges of 3D content are significant obstacles to law enforcement. Existing regulations, including Law No. 17 of 2016 concerning Child Protection, Law No. 1 of 2024 concerning the Second Amendment to the ITE Law, and Law No. 12 of 2022 concerning the TPKS, have provided a strong legal basis, but do not specifically regulate AR/VR technology. A normative juridical research method with a statutory and conceptual approach is used to analyze existing norms, regulatory gaps, and their relevance to international standards such as the Budapest Convention and the Lanzarote Convention. The research findings emphasize the urgency of adaptive regulatory updates to technological developments, the implementation of cybersecurity standards, mandatory age verification, and strengthening the capacity of law enforcement officers in digital investigations and AR/VR forensics. Cross-border and cross-sector collaboration is needed to expedite notice and takedown mechanisms and close legal loopholes exploited by perpetrators. These efforts are expected to create a safe digital environment for children and increase the effectiveness of legal protection in the realm of immersive technology.